2014
DOI: 10.1016/j.drugalcdep.2014.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the size of the population of persons who inject drugs in the island of Montréal, Canada, using a six-source capture–recapture model

Abstract: Background: To plan and implement services to persons who inject drugs (PWID), knowing their number is essential. For the island of Montréal, Canada, the only estimate, of 11 700 PWID, was obtained in 1996 through a capture-recapture method. Thirteen years later, this study was undertaken to produce a new estimate.Methods: PWID were defined as individuals aged 14-65 years, having injected recently and living on the island of Montréal. The study period was 07/01/2009 to 06/30/2010. An estimate was produced usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…As has been done in other capture-recapture studies, we attempted to relax this assumption by focusing on a well-defined time window with which to estimate the population size (calendar year 2013). [27,28] The death registry indicates that ours is not a true closed population; 57 PLWH died in 2013, 16 of whom did not appear on any other list included in this analysis. However, there were no temporal constraints on any of the lists included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As has been done in other capture-recapture studies, we attempted to relax this assumption by focusing on a well-defined time window with which to estimate the population size (calendar year 2013). [27,28] The death registry indicates that ours is not a true closed population; 57 PLWH died in 2013, 16 of whom did not appear on any other list included in this analysis. However, there were no temporal constraints on any of the lists included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The starting population is Montréal’s active PWID population (i.e., people who injected in the past 6 months), estimated to be 4,000 individuals [ 2 ]. Due to limited data regarding the evolution of the population size of PWID in Montréal, the population size is assumed constant in time: each dead PWID is replaced in the model by another non-infected PWID.…”
Section: Methodsmentioning
confidence: 99%
“…Drug injection is the main transmission route for hepatitis C virus (HCV) in high income countries [ 1 ]. The number of active people who inject drugs (PWID) (defined as injecting in the past six months) in Montréal is estimated to be 4,000 [ 2 ]. According to regional surveillance data (SurvUDI network), approximately 70% of this population has been exposed (antibody positive) to HCV [ 3 ] and the number of new infections remains high: 22.1/100 persons-years (PY) for the 2010–2013 period (unpublished SurvUDI data).…”
Section: Introductionmentioning
confidence: 99%
“…In Montreal, a recent study estimated the size of the PWID population for 2009 to 2010. 22 Based on the capture-recapture method, the study reported an estimated 3910 PWID, representing 2.8 PWID per 1000 residents aged 14 to 65 years for the period between July 1, 2009 and June 30, 2010. This is one-third of the estimated 11,700 PWID obtained in 1996.…”
Section: Drug Injection: Epidemiological Trends In Canada and Abroadmentioning
confidence: 99%